2012
DOI: 10.1161/circulationaha.111.041814
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Autophagosome Clearance Contributes to Cardiomyocyte Death in Ischemia/Reperfusion Injury

Abstract: Background In myocardial ischemia, induction of autophagy via the AMP-induced protein kinase (AMPK) pathway is protective, whereas reperfusion stimulates autophagy with BECLIN-1 upregulation, and is implicated in causing cell death. We examined flux through the macro-autophagy pathway as a determinant of the discrepant outcomes in cardiomyocyte cell death in this setting Methods and Results Reversible left anterior descending coronary artery ligation was performed in mice with cardiomyocyte-restricted expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

30
415
2
5

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 428 publications
(452 citation statements)
references
References 36 publications
30
415
2
5
Order By: Relevance
“…Beclin 1 is a well-known key regulator of autophagy, 34,35 and recent studies have shown that Beclin 1 mediates the autophagic cell death in cardiomyocytes. 36 Our results also showed that knockdown of Beclin 1 attenuated autophagy (Supplementary Figure 3A) and cell death (Supplementary Figure 3B). Overexpression of Beclin 1 sensitized cells to undergo death, and increased cell death was observed upon both A/R and Beclin 1 treatment in the presence of a lysosomal inhibitor bafilomycin A1 (Supplementary Figure 3C).…”
Section: Resultssupporting
confidence: 67%
“…Beclin 1 is a well-known key regulator of autophagy, 34,35 and recent studies have shown that Beclin 1 mediates the autophagic cell death in cardiomyocytes. 36 Our results also showed that knockdown of Beclin 1 attenuated autophagy (Supplementary Figure 3A) and cell death (Supplementary Figure 3B). Overexpression of Beclin 1 sensitized cells to undergo death, and increased cell death was observed upon both A/R and Beclin 1 treatment in the presence of a lysosomal inhibitor bafilomycin A1 (Supplementary Figure 3C).…”
Section: Resultssupporting
confidence: 67%
“…We next determined whether repetitive starvation would offer cytoprotection to HR-induced cell death. 36 Interestingly, 2 cycles of repetitive starvation were associated with a modest (and statistically significant) »13% to 15% reduction in HRinduced cell death (Fig. 12E and F).…”
Section: Fasting and Refeeding Transcriptionally Modulate The Autophamentioning
confidence: 89%
“…Indeed, we have previously found that transcriptional suppression of the autophagy machinery with reperfusion-induced accumulation of BECN1 explains the lack of a protective role of the observed extent of autophagy induction in cardiac ischemia-reperfusion injury. 36,68 Further insights into this process could be gleaned via careful examination of the effects of intermittent fasting on the transcriptional program of the injured myocardium, in future studies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations